Removing Copper from Contaminated Water Using Activated Carbon Sorbent by Continuous Flow - M.H. Salmani; M.H. Ehrampoush; S. Sheikhalishahi; M. Dehvari (Shahid Sadoughi University of Medical Sciences, 2012)
Introduction: A major concern of human being is accumulation and toxicity of heavy metals in their body. Copper is a heavy metal ion that in concentration of 2 mg/l can cause numerous complications. Different treatment methods have been proposed for removing metals from contaminated water by researchers. Among these methods, sorption seems a better method with high removal efficiency. In this study, conditions for removal of copper ions by activated carbon sorbent were studied with continuous flow. Materials & Methods: This was a laboratory - experimental study. A 20mg/l solution of copper ions was prepared and passed through a 5 × 10 cm column with average output rate of 1.85 ml/min. Output of column was sampled every 30 minutes and the remaining amount of copper ion in each sample was measured by flame atomic absorption. Results: The empty bed volume (EBV) was equal to 138 ml. The highest removal efficiency was 99.7 percent at 127 minutes. From equilibrium time, the removal efficiency was constant with time. The adsorption capacity of activated carbon was 0.25mg.g-1. The isotherm study indicated that the sorption data can be obeyed by both Langmuir and Freundlich isotherms (R2>0.95) but Langmuir model had higher agreement with this experimental data (R2= 0.988). Conclusion: The binding of ions to the sorbent in the adsorption process is extremely important. For this column 62.5 minutes after filling was appropriate, so the highest removal efficiency was obtained. Equilibrium time was dependent on the speed of influent through the column in the continuous flow. For selected column, the rate of 1.85 ml/min is a good performance.